If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3r = 5r + 9 Reorder the terms: 5 + 3r = 9 + 5r Solving 5 + 3r = 9 + 5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5r' to each side of the equation. 5 + 3r + -5r = 9 + 5r + -5r Combine like terms: 3r + -5r = -2r 5 + -2r = 9 + 5r + -5r Combine like terms: 5r + -5r = 0 5 + -2r = 9 + 0 5 + -2r = 9 Add '-5' to each side of the equation. 5 + -5 + -2r = 9 + -5 Combine like terms: 5 + -5 = 0 0 + -2r = 9 + -5 -2r = 9 + -5 Combine like terms: 9 + -5 = 4 -2r = 4 Divide each side by '-2'. r = -2 Simplifying r = -2
| 11x-(12x-7)= | | 2u+5(u+6)=12 | | 9x+3/4y-6x | | 49(x+1/4)^2=100 | | 8*.75=f | | 6*.75=s | | 8x+4=11x-17 | | 25.25/8=s | | -2=M(3)+B | | (1/x)+((2x+3)/2)=8x | | -.6666x+10=.333x+8-16 | | 81/8-25/6 | | .75-20=s | | 23x=o | | 6x-22=-7+4 | | 3x+21=6x+15 | | 11x+4=2(4x+1)-x+7 | | 3/x+5/9x^2 | | AX^6-X^6+6A-6=0 | | 6x+3+x=1+2x+7 | | -4z+2=5z-3 | | .6666x+10=.333x+8-16 | | 8-7(3y-2)= | | 328.1x.63= | | 10x+32=-16 | | (x+5)(2x-6)=x | | 6=15-3x | | H(x)=2x^2-6x-36 | | 6x+4(5-3x)=2 | | 2x+2(x-3)=91.50 | | x=35/5 | | 2(x-2)+3x=91.50 |